Analisis Ontologi Pengembangan Kehidupan Beragama dalam Bimbingan dan Konseling - Prawita, Citra Bella; Jamaris; Solfema (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
Religion is very important for human life. Religion and life is an attractive topic in daily discussion because it can be reached in the science of ontology. Most people think that clients commit crimes because they lack religious and moral knowledge. So that the role of the counselor who carries out counseling must understand and understand how to guide clients and solve their problems based on religion by analyzing them ontologically. The method used in this research is descriptive research with a qualitative approach. The data collected in this study is using the documentation method. In this study, data analysis follows Miles & Huberman guidelines, namely data collection, data display, data reduction and conclusions. Someone with religious instincts will be aware of the concepts and conditions regarding the potential to know God. Religion can provide a sense of security, peace and happiness to every adherent. Happiness will activate the beta endorphins. The solution to every problem regarding the soul in religion, especially the Islamic religion, so that a healthy and positive soul is maintained is by going through everything that has become an obligation in following orders and avoiding oneself from the prohibitions that have been set by Allah SWT.